Montanism: A Local, Popular, Apocalyptic Reform Movement in Early Christianity - Decock, Paul Bernard (Neotestamentica, 2025)
The aim of the paper is to focus on Montanism in its early decades and to situate three of the much-disputed aspects of the movement within the wider context of Early Christianity, namely, prophecy, eschatology, and their novel, more rigorous, moral rules. Montanism can be seen as a popular type of an Early Christian reform movement with a local, Phrygian touch, a "millenarian" movement of the conversionist type, with strong emphasis on moral purity. Montanism embodied in its own way the message of Mark 1:15: πεπλήρωται ὁ καιρὸς καὶ ἤγγικεν ἡ βασιλεία τοῦ θεοῦ· μετανοεῖτε καὶ πιστεύετε ἐν τῷ εὐαγγελίῳ.